Knowledge of Cotton Growers about Integrated Weed Management Practices - Barkade , A.T.; Lahariya, K.T.; Koshti , N.R.; Mankar, D. M. (Indian Journal of Extension Education, 2017)
The present study was undertaken in Karanja and Manora Panchayat Samitis of Washim district in Vidarbha region of  Maharashtra State. The findings revealed that majority of respondents belonged to middle age group ; educated up to  college level; had middle family size (4 to 6 members), belonged to semi-medium size land holding category and agriculture was the main occupation, with annual income between of ` 1,00,001 to 2,00,000, had bi-seasonal  cropping system, put up to 1.01 to 2.00 ha area under cotton crop; had medium sources of information; had medium  category of extension contact; had medium level of economic motivation;, had medium level of knowledge and  adoption of integrated weed management practices. As regards the correlation analysis, independent variables namely  education, land holding, annual income, cropping pattern, area under cotton crop, sources of information, extension  contact and economic motivation showed a positive and highly significant correlation with knowledge of the  respondents at 0.01 level of probability. Whereas, the characteristics such as age, family size, occupation had shown  negative and non contributory effect with knowledge of the respondents.
Keywords: Knowledge; Cotton Growers; Integrated Weed Management